Community resilience through partnership after the Great East Japan Earthquake: cooking classes by Iwate Co-op and a food company - Ito, Naomi; Konno, Kayoko; Nozaki, Kumiko; Fukushi, Kumiko; Kanno, Kasumi; Kawamura, Hiromi; Nakamura, Yayoi; Yamada, Mikio; Kuroda, Ai; Kuchii, Toshiya; Kinoshita, Yuri; Nabetani, Teru; et al. (Frontiers in Public Health, 2024)
Introduction: This case study aimed to demonstrate how cooking class activities held in collaboration with the Ajinomoto Foundation (TAF) and a consumer cooperative after the Great East Japan Earthquake contributed to the resilience of the affected community. Methods: With reference to the logic model, evaluation indicators for the case study were established. We focused on the Iwate Seikatsu Kyodo Kumiai (Iwate Co-op). We organized 120 continuation cases out of the eight-and-ahalf-year activity records of the project owned by TAF (April 2012 to March 2020). The Iwate Co-op was one of the 120 continuing cases and had special features, including awareness that its members were responsible for the community. Results: The collaboration revealed three effects. First, owing to the encounter and collaboration with TAF, the cooking class was continuously conducted even after TAF withdrew from the disaster-affected areas. Second, the Iwate Co-op trained some of its members as food support staff to run the cooking class independently and was actively involved in obtaining the necessary budget for the operation, consequently leading to the independent activation of member activities. Third, they developed a cooking class project in inland areas other than disaster-stricken areas, assuming that they could incorporate the project into their existing activities, as food problems affected people beyond disaster victims. Conclusion: The collaborative food support project of the Iwate Co-op and TAF contributed to the resilience of the affected people and communities by strengthening bonds and solidarity among residents and organizations. The key to success was the fusion of a traditional sense of independence in the co-op with TAF's mission and technical know-how. The partnership between the Iwate Co-op and TAF allowed the former to aim towards developing food support activities in the affected areas, accelerating the resilience of the community in the Iwate Prefecture.